Awareness and willingness of Muslims regarding Islamic banking products and services in Kazakhstan - Omarov, Daniyar (Institute of Islamic Banking and Finance, .International Islamic University Malaysia, 2013)
Islamic banking was an abstract concept until the first half of the twentieth century. In Kazakhstan, it has been only three years since the first Islamic bank made its debut. Islamic banks have to compete with their rival, conventional banks, which have far longer history than Islamic banks. Due to this competition, Islamic banks have to know the awareness, understanding and willingness of Kazakhs towards it. Islamic banks are not only available for Muslims, but they are also available for non-Muslims as well. In Kazakhstan 65 percent of the population are Muslims, and this is a significant factor for the Islamic banks. The purpose of this research is to examine the level of awareness, understanding and willingness of Muslims to patronize Islamic banking in Kazakhstan. Thus, a total number of 300 respondents from different cities of Kazakhstan were selected for the purpose of this study. For the analysis, AN OVA and Pearson Correlation Coefficient methods were adopted. The results show that more than half of the respondents are aware of Islamic banking in Kazakhstan, but they are not aware of most of the products and services offered by Islamic banks. Kazakhs' level of understanding towards Islamic bank concepts are at moderate level, but the perception of the Kazakhs on Islamic banking is very high. This study also provides theoretical and managerial implications to the Islamic bankers to attract Kazakh customers and recommendations for the future research on Islamic banking in Kazakhstan